A Phase IC Study Evaluating the Safety, Tolerability, Pharmacokinetics, and Cognitive Outcomes of BI 409306 in Patients with Mild-to-Moderate Schizophrenia. Issue 1 (June 2018) - Brown, David; Daniels, Kristen; Pichereau, Solen; Sand, Michael
Abstract Introduction This randomized, double-blind, parallel-group study investigated the safety, tolerability, pharmacokinetics (PK), and cognitive outcomes of BI 409306—a selective phosphodiesterase 9A (PDE9A) inhibitor—in patients with schizophrenia. Methods Patients with mild-to-moderate schizophrenia were randomized (1:1:1:1) to receive BI 409306 at 25, 50, or 100 mg or placebo once daily over 14 days. The primary endpoints were safety and tolerability; the secondary endpoints were PK and cognitive outcomes. Results Of the 40 randomized patients, 38 (95%) completed the study. Patients were predominantly male (87.5%; mean age, 40.2 years). After a single dose, C max was reached within 30–45 min. The geometric mean (gMean)C max and AUC0-∞ ranged from 138 to 998 nmol/L and 217 to 2020 nmol∙h/L, respectively. Elimination was rapid (gMeant 1/2 range 1.10–1.85 h). After multiple doses, C max, ss was reached within 1 h; elimination was similar to that observed after a single dose. Total exposure at steady state and after a single dose were similar (accumulation ratio range: AUC, 0.758–1.13 and Cmax, 0.768–1.40). No deaths, adverse events (AEs) leading to discontinuation, or serious AEs were observed. Treatment-emergent AEs were mild, with no apparent dose-related trends. There was no worsening of schizophrenia symptoms (Positive and Negative Syndrome Scale) and no trends in suicidality (Columbia Suicide Severity Rating Scale). The Hopkins Verbal Learning Test–Revised (HVLT-R) and Brief Visuospatial Memory Test–Revised (BVMT-R) showed no effect on cognitive function. Conclusion Administration of BI 409306 in patients with mild-to-moderate schizophrenia resulted in satisfactory safety and tolerability. BI 409306, PK was characterized by rapid absorption, monophasic to biphasic elimination, and minor accumulation with multiple dosing. Trial Registration ClinicalTrials.gov identifier NCT01892384. Funding Boehringer Ingelheim Pharma GmbH & Co. KG.